Relative Effectiveness of Bilateral and Multilateral Aid on Development Outcomes. Issue 4 (27th December 2016) - Biscaye, Pierre E.; Reynolds, Travis W.; Anderson, C. Leigh
Abstract: Aid donors are interested in understanding whether allocating aid via bilateral or multilateral channels might be more effective for achieving development goals. We review 45 papers that empirically test the associations between bilateral and multilateral aid flows and various development outcomes including gross domestic product growth, governance indicators, human development indicators and levels of non‐aid investment flows. Findings suggest that differences between countries and regions, time periods, aid objectives, and individual donor organizations all may influence the effectiveness of aid delivered bilaterally and multilaterally. We find, however, no consistent evidence that either bilateral or multilateral aid is more effective overall.